126k views
4 votes
Multiply. start fraction k plus 3 over 4 k minus 2 end fraction dot left parenthesis 12 k squared plus 2 k minus 4 right parenthesis

User Buga
by
4.7k points

1 Answer

4 votes

Answer:


\therefore ((k+3))/((4k-2)).(12k^2+2k-4)=3k^2+11k+6

Explanation:

Factorization of a Quadratic polynomial:

  • In order to factorize
    ax^2+bx+c we have to find out the numbers p and q such that, p+q = b and pq=ac.
  • Finding the two integers p and q, we rewrite the middle term of the quadratic as px+qx. Then by grouping of the terms we can get desired factors.

Multiplication of two binomial:

(a+b)(c+d)

=a(c+d)+b(c+d)

=(ac+ad)+(bc+bd)

=ac+ad+bc+bd

Given that,


((k+3))/((4k-2)).(12k^2+2k-4)


=((k+3))/(2(2k-1)).2(6k^2+k-2) [ taking common 2]


=((k+3))/((2k-1)).(6k^2+k-2) [ cancel 2]


=((k+3))/((2k-1)).(6k^2+4k-3k-2)


=((k+3))/((2k-1)).\{2k(3k+2)-1(3k+2)\}


=((k+3))/((2k-1)).(3k+2)(2k-1)


=(k+3).(3k+2)


=3k^2+9k+2k+6


=3k^2+11k+6


\therefore ((k+3))/((4k-2)).(12k^2+2k-4)=3k^2+11k+6

User Cootri
by
4.8k points